Scrooge Posing as Mother Teresa: How Hypocritical Social Responsibility Strategies Hurt Employees and Firms - Scheidler, Sabrina (Journal of business ethics, 2019)
Extant research provides compelling conceptual and empirical arguments that company-external (e.g., philanthropic) as well as company-internal (i.e., employee-directed) CSR efforts positively affect employees, but does so largely in studies assessing effects from the two CSR types independently of each other. In contrast, this paper investigates external–internal CSR jointly, examining the effects of (in)consistent external–internal CSR strategies on employee attitudes, intentions, and behaviors. The research takes a social and moral identification theory view and advances the core hypothesis that inconsistent CSR strategies, defined as favoring external over internal stakeholders, trigger employees’ perceptions of corporate hypocrisy which, in turn, lead to emotional exhaustion and turnover. In Study 1, a cross-industry employee survey (n = 3410) indicates that inconsistent CSR strategies with larger external than internal efforts increase employees’ turnover intentions via perceived corporate hypocrisy and emotional exhaustion. In Study 2, a multi-source secondary dataset (n = 1902) demonstrates that inconsistent CSR strategies increase firms’ actual employee turnover. Combined, the two studies demonstrate the importance of taking into account the interests of both external and internal stakeholders of the firm when researching and managing CSR.